“Oh, the places you'll go!”—But not for those children trapped by family violence - Zentveld, Elisa (Frontiers in Sustainable Tourism, 2023)
Tourism is often regarded as an opportunity to “get away” and “escape;” a time for rest and relaxation and “getting away from it all.” Traveling to new places is also thought to be an important “classroom” for children. Traveling to new places was a theme in books by the famous children's author and illustrator Theodor Seuss Geisel (who published under the name “Dr. Seuss”). Whilst Dr. Seuss had numerous hardships in his life including a prolonged illness, no children, and his first wife's suicide, he wrote books that were considered uplifting and fun to read. In the Dr. Seuss book “Oh, the places you'll go!” he wrote “you're off to great places! Today is your day! Your mountain is waiting, so….get on your way!” The idea that children should feel free to visit great places, experience life to its fullest, and feel safe seems on the surface to be axiomatic. Sadly, this is not the experience for all children. Taking a whole tourism systems approach, this paper outlines how family violence impacts each of the five elements in the tourism system. Whilst tourism studies often focus on the positive and boosterish side, to fully understand children in tourism, it is necessary to look at it in its entirety. This means acknowledging and understanding how children's tourism experiences might be limited. This paper reveals that children can be denied permission to undertake certain travel due to court orders or denial by the perpetrator of family violence. It is hoped that greater awareness of this topic may result in better and fairer family law orders to allow more tourism experiences for children who live with or have lived with family violence.